PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU DI SEKOLAH DASAR - Mardiani, Mardiani; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem in this study is whether using card media can improve the preliminary reading skills which include the reasonableness of pronunciation, the fairness of intonation, and fluency in Al-Karima Integrated Islamic Elementary School? The general objective of this study is to improve the initial reading skills which include the reasonableness of pronunciation, the reasonableness of intonation, and fluency by using card media in Al-Karima Integrated Islamic Primary School Class I.This study uses descriptive methods with the form of classroom action research, and the nature of research is collaborative. The research setting took place at Al-Karima Integrated Islamic Elementary School in Southeast Pontianak with research subjects namely class I students totaling 20 people. Data collection techniques used are interview techniques, direct observation techniques, measurement techniques with data collection tools namely observation sheets. The data collected is analyzed by an average calculation.This research was conducted in 2 cycles. The results obtained were the ability of the teacher to design RPP to improve the preliminary reading skills of cycle 1, which was 2.84 with a sufficient category of improvement in cycle 2 to 3.11 with a good category. The ability of the teacher to carry out learning to improve the initial reading skills in cycle 1 was 2.40 with an adequate category of improvement in cycle 2 to 3.13 with a good category having an increase of 0.73. The skills of beginning reading students have increased each cycle. In cycle 1 the average value of students was 82. While in cycle 2 the average value of students became 91 increased by 9. Thus it can be concluded that the use of card media in learning can improve students' initial reading skills.Â Keywords: Early Reading Skills, Indonesian Language